Sedentary Behaviour and Physical Activity Levels during Second Period of Lockdown in Chilean's Schoolchildren: How Bad Is It? - Ricardo Martínez-Flores; Ignacio Castillo Cañete; Vicente Pérez Marholz; Valentina Marín Trincado; Carolina Fernández Guzmán; Rodrigo Fuentes Figueroa; Gabriela Carrasco Mieres; Maximiliano González Rodríguez; Fernando Rodriguez-Rodriguez (MDPI AG, 2023)
Objective. The objective of this study was to compare the levels of sedentary behaviour and physical activity in relation to sociodemographic variables of Chilean schoolchildren before and during the COVID-19 pandemic. Methods. This retrospective study considered a non-random sample of 83 boys and 232 girls, and their respective parents, who attended public schools (n = 119) and private schools (n = 196) in Chile. A self-report instrument was applied that included sociodemographic variables, sedentary behaviour (SB), and physical activity (PA) in the second period of the pandemic in 2021. Results. The main results show that pre-pandemic SB had significant differences when compared between sexes, except for television time. During the pandemic, there was no significant difference in television time or telephone time. There were no significant differences by sex before and during the pandemic. When comparing the SB scores, video game time in boys decreased (p < 0.001), as did video game time in girls (p < 0.001), and computer time in boys (p < 0.001) and girls (p < 0.001). Telephone time increased in boys (p < 0.001) and girls (p < 0.001), as did television time (p < 0.001). Likewise, PA increased in boys (Δ + 9.51min) and girls (Δ + 3.54 min) during the pandemic (p < 0.001). Conclusions. Both PA and SB underwent changes according to sex before and during the second period of the COVID-19 pandemic in Chilean schoolchildren.